An Overview of Knowledge and Attitude About Premenstrual Syndrome on 9th Grade Students at Junior High School Number 1 West Selemadeg - Della amelia putri; Nurul Azmi Aprianti (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Background: Culture plays a significant role in shaping the habits, beliefs, and health decisions during pregnancy. Cultural practices can support maternal and fetal health, but they can also potentially pose risks, such as unhealthy diets or excessive physical activity. Studies in Ethiopia and Tanzania have shown that cultural habits can hinder access to modern healthcare services. Therefore, a deep understanding of the local culture is crucial for designing culturally sensitive health interventions. Objective: To enhance understanding and awareness of pregnancy, especially high-risk pregnancies, by considering the cultural influences on habits, beliefs, and health decisions made by mothers to support the optimal well-being of mothers and babies. Methods: This study utilized a scoping review design based on PRISMA guidelines. A total of 27.454 articles were identified and screened based on inclusion criteria, which included publications from 2020 to 2024 and available in full-text format. Results: The analysis revealed that culture plays a crucial role in influencing the health and behavior of pregnant women. Various cultural practices can promote health but may also pose risks. From the 15 articles analyzed, patterns emerged showing how traditions, norms, and beliefs influence health decisions, dietary patterns, and access to healthcare services. Conclusion: Understanding the cultural influences in the context of pregnancy is critical. Culturally-based and collaborative health interventions can help address the challenges faced by pregnant women, especially those at high risk. By considering cultural values and traditional practices, healthcare services can become more effective and relevant, supporting the health of mothers and the optimal development of the fetus.